Planting precision evaluation of two garlic seeders - Rocha, Francisco E. de C.; Oliveira, Carlos A. da S. (Pesquisa Agropecuaria Brasileira, 1992)
Two garlic seeders were developed and evaluate. One of them used a spiral type mechanism (prototype A) and the other, a conveyor lug belt (prototype B) as a clove distribution system. Prototype A was tested with small and large cloves and prototype B, with nonclassified cloves and two sprocket wheel combinations. The percentage of long spacing (gaps) and short spacing (double cloves) between two cloves were smaller with the conveyor lug belt type mechanism. The percentage of aceptable spacing hill was 20% bigger for prototype B.